Death and glory - Thomas, Will, 1958- (Thomas, Will, 1958- Barker & Llewelyn novel, 2024)
"In 1894, Cyrus Barker, London's premier enquiry agent, is entangled in a conspiracy to revive the American Civil War by prominent figures, long believed deceased. Private Enquiry agent Cyrus Barker, along with his partner Thomas Llewelyn, has a long, accomplished history - he's taken on cases for Scotland Yard, the Foreign Office, and even the crown itself, fulfilling them all with great skill and discretion. None of those cases, however, are as delicate and complicated as the one laid before him by a delegation of men who, thirty years before, fought for the Confederacy during the American Civil War. These men want to revive the Confederacy with a warship promised to the Rebels from the British Government in 1865. To get it now, they're threatening to reveal the long-secret treaty with the Confederacy. Barker is hired to use his connections to discreetly bring their threats to the Prime Minister. With a web of prominent, if secret, supporters throughout England ready to through their support to their efforts to wage war anew on the United States, the delegates are just waiting for the warship to begin their plans. But some of the men are not who they claim to be, and the American government has their own team watching, and waiting, for the right moment to take action. As this fuse on this powder keg of a situation grows ever shorter, it's up to Barker & Llewelyn to uncover the real identities and plans of these dangerous men"--